Needs Analysis for PBL-Based Mathematics Student Worksheet at SMPN L Sidoharjo - Eryani, Rita; Pandra, Viktor; Sulistiyono, Sulistiyono (Journal of English Language and Education, 2025)
This study aims to analyze the needs for developing mathematics student worksheets (Student Worksheet) based on the Problem-Based Learning (PBL) approach at SMPN L Sidoharjo. The research was motivated by the growing awareness among educators of the importance of innovative learning tools that foster critical thinking, collaboration, and active student involvement. Using a qualitative descriptive method, data were collected through interviews, questionnaires, and classroom observations involving mathematics teachers and students. The results show a strong readiness and enthusiasm from both teachers and students toward the implementation of PBL-based learning. While the existing Student Worksheets still require improvement, there is already a foundation of supportive teaching practices and student openness to problem-based learning activities. The study concludes that the school environment is highly conducive to the integration of PBL in mathematics instruction. These findings support the development of Student Worksheets that are not only aligned with curriculum goals but also responsive to the needs and potentials of students at SMPN L Sidoharjo.